Worship Leader Training (Theory and Practice) for Lay Pastoral Servants at the Sacred Heart of Jesus Parish, Tomohon - Singal, Fecky Evendy (International Journal of Social Service and Research, 2023)
Lay Pastoral Ministers (PPA) are laity who are called and sent among the faithful and the community to carry out the pastoral care of the local Church. PPA in the Parish of the Sacred Heart of Jesus Tomohon, specifically ministers in the field of spirituality numbered approximately 153 people spread across 51 groups of people called spiritual areas. The Spiritual Area is a Church Base Community (KBG) consisting of 30-40 families whose number of people is around 90-125 people per KBG. Thus, PPA in the Parish of the Sacred Heart of Jesus serves approximately 4,229 people. One form of service is the Liturgical Apostolic in the form of the Worship of the Word which is held regularly and other Worship such as the Thanksgiving Service and the Worship of the Spirits which are held in due time. Facing the needs of worship services, both held regularly and at any time, PPA generally has difficulties when it comes to leading worship. In general, they still use the old Code of Worship because PPAs have not received socialization and training on the use of the new Code of Worship formulation. Departing from the above problems, through this Faith-Based Community Service activity, the service and team and also through collaboration with the Spiritual Field of the Pastoral Council at the Sacred Heart of Jesus Tomohon Parish, will organize training activities for PPA, especially about leading worship. With the implementation of this training, it is expected to have a good and effective impact on PPA and other participants and also provide knowledge and skills so that worship in each KBG can be carried out properly and the faith of the people will grow and develop..